Assessment Tasks in Chemistry - TIMOFTE, Roxana S. (2019)
Assessment plays an important role in education and the teachers andacademics should be aware of the different strategies used for thedevelopment of assessment tasks. Herein are presented assessment tasksdeveloped by using different strategies: by using a competency model andby using a learning taxonomy.